Design & Construction Of Pile Foundations For A Building Complex - A Case History - S. K. V. Avasarala (Deep Foundations Institute, 1995)
This paper presents a case history of design, prediction, probe and production pile driving monitoring, loading tests and installation of over 3,300 prestressed concrete piles for a building complex consisting of 12, 5- and 6-story over parking buildings. The project was recently completed in three-phases over a span of 4 years. The subsoil conditions were explored by performing 25, Standard Penetration Test (SPT) borings throughout the site. Various types of driven pile foundations were considered and following an evaluation of high structural loads and site-specific constraints such as variable depth of bearing layer of Florida limestone and quality of clay and limestone layers, a prestressed concrete pile support system was selected as the most economical and effective foundation approach. The building foundations were designed for a pile capacity of 353 kN (40 tons) in compression, 45 kN (5 tons) in lateral capacity for a deflection of 0.64 cm (0.25 in.), and 133 kN (15 tons) in uplift capacity. The axial and lateral allowable pile capacity and lengths were predicted using SPT91 and LPILE computer programs, which are generally used in Florida. The validation of these capacities was derived from 144 probe piles and performance of 12 pile loading tests on selected probe piles. Prior to installation of probe or production piles, a termination criterion was established using 1-dimensional wave equation analyses in addition to the design pile embedment requirement. The predicted pile capacities compared very well with the capacities from the loading tests on probe piles. This information was effectively utilized as part of the overall quality control program to install a total of 4,186 prestressed concrete piles (including 144 probe piles) in different building areas across the project site to depths ranging from 8 to 21 m (25 to 90 ft) below existing ground elevation as part of foundation support system. This engineered, monitored, and tested foundation solution provided an effective and satisfactory basis for completion and approval of the foundation work for this 12, 5- and 6-story over parking building complex. A recent reconnaissance has indicated that all the building foundations are performing satisfactorily.